2018
DOI: 10.1245/s10434-018-6558-7
|View full text |Cite
|
Sign up to set email alerts
|

Implications of the Pattern of Disease Recurrence on Survival Following Pancreatectomy for Pancreatic Ductal Adenocarcinoma

Abstract: Background. After radical resection of pancreatic ductal adenocarcinoma (PDAC), approximately 80% of patients will develop disease recurrence. It remains unclear to what extent the location of recurrence carries prognostic significance. Additionally, stratifying the pattern of recurrence may lead to a deeper understanding of the heterogeneous biological behavior of PDAC. Objective. The aim of this study was to characterize the relationship of recurrence patterns with survival in patients with resected PDAC. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
56
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(69 citation statements)
references
References 27 publications
(24 reference statements)
6
56
0
Order By: Relevance
“…22 Similarly, multiple studies have shown that lung-only recurrence after PDAC resection results in superior survival when compared to other recurrence patterns, such as liver-only, peritoneal or multiple-site recurrence. [10][11][12]20 The OS for patients with pulmonary recurrence in these studies (median 36 12 , 36 20 , and 40 11 months) was remarkably similar to the 40 months found in the current study, further supporting the hypothesis that favorable tumor biology exists in these patients.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…22 Similarly, multiple studies have shown that lung-only recurrence after PDAC resection results in superior survival when compared to other recurrence patterns, such as liver-only, peritoneal or multiple-site recurrence. [10][11][12]20 The OS for patients with pulmonary recurrence in these studies (median 36 12 , 36 20 , and 40 11 months) was remarkably similar to the 40 months found in the current study, further supporting the hypothesis that favorable tumor biology exists in these patients.…”
Section: Discussionsupporting
confidence: 85%
“…5 However, recent evidence suggests that recurrent PDAC displays diverse behaviors based on recurrence timing and location. [6][7][8][9][10] These differences potentially provide a basis for a more individualized approach to the treatment of recurrence. Isolated pulmonary recurrence in particular has been associated with prolonged survival when compared to recurrence at other sites.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have linked specific recurrence locations to different predictive factors, including R1 resection margin and low‐grade tumour differentiation. In addition, various sites of initial recurrence may be associated with different survival rates. For example, lung relapse as the first location occurs later than recurrence in the liver or at other sites.…”
Section: Introductionmentioning
confidence: 99%
“…Since not all PDAC patients recur in the same manner, understanding the pattern, timing, and implications of recurrence is critical to the planning of adjuvant strategies. In addition, clinicopathologic risk factors for predicting failure patterns could potentially allow individualized and more effective adjuvant therapy strategies [17,18]. However, to our best knowledge, there is no published studies to specially investigate the risk predictor factors for isolated LRR in PDCA patients by using competing risk regression model, and the patterns of local regional recurrence of lymph node are remains undetermined.…”
Section: Discussionmentioning
confidence: 99%